Legal and regulatory framework of Islamic banking in Libya - Belal, Zainab; Hassan, Rusni (Sekolah Tinggi Ilmu Syariah Husnul Khotimah (STIS HK), 2018)
Banking regulatory framework is a mandatory requirement to ensure sound and effective financial sector, hence, the overall development of the country. The growing demand for Islamic Banking products and services, in Libya, needs to be accompanied with effective regulatory framework to protect the rights of all share/stakeholders and assures Islamic banking development. This study examines the regulatory framework for Islamic banks in Libya in terms of the regulatory authorities, banking laws, Shari’ah governance and dispute resolutions. The study reveals there is still no specific and independent law on Islamic finance in Libya as the case for conventional banks. Therefore, there is a desperate need to establish a comprehensive regulatory framework for Islamic finance industry with the aim to enhance the development of financial investment in Islamic finance. The study also highlights in more details the Banking laws development for Islamic banking from 2005 until 2013.The paper also discloses that arbitration is the best method that can be used for dispute resolution due to lack of availability of specialized judges.